The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1126/science.1104909
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy at Meridiani Planum from the Mini-TES Experiment on the Opportunity Rover

Abstract: The Miniature Thermal Emission Spectrometer (Mini-TES) on Opportunity investigated the mineral abundances and compositions of outcrops, rocks, and soils at Meridiani Planum. Coarse crystalline hematite and olivine-rich basaltic sands were observed as predicted from orbital TES spectroscopy. Outcrops of aqueous origin are composed of 15 to 35% by volume magnesium and calcium sulfates [a high-silica component modeled as a combination of glass, feldspar, and sheet silicates (approximately 20 to 30%)], and hematit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
281
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 386 publications
(294 citation statements)
references
References 39 publications
12
281
0
1
Order By: Relevance
“…TIR measurements of this dust from orbit and by the two Miniature Thermal Emission Spectrometers (Mini-TES) onboard the Mars Exploration Rovers (MER) have demonstrated a common spectral character that suggests uniform mineralogy and particle size wherever the dust is observed (Christensen et al 2004;Yen et al 2005). Bandfield et al (2003) measured TIR spectra of physical mixtures of labradorite as a proxy for martian dust combined with various carbonate minerals and found that a small amount (∼2 to 5 weight %) of fine-particulate magnesite (<10 micron) provided the best fit to distinctive features above 1300 cm −1 in TES spectra of dust.…”
Section: Carbonates In Martian Dustmentioning
confidence: 99%
“…TIR measurements of this dust from orbit and by the two Miniature Thermal Emission Spectrometers (Mini-TES) onboard the Mars Exploration Rovers (MER) have demonstrated a common spectral character that suggests uniform mineralogy and particle size wherever the dust is observed (Christensen et al 2004;Yen et al 2005). Bandfield et al (2003) measured TIR spectra of physical mixtures of labradorite as a proxy for martian dust combined with various carbonate minerals and found that a small amount (∼2 to 5 weight %) of fine-particulate magnesite (<10 micron) provided the best fit to distinctive features above 1300 cm −1 in TES spectra of dust.…”
Section: Carbonates In Martian Dustmentioning
confidence: 99%
“…The Mars Exploration Rovers Opportunity and Spirit have contributed our first-ever geologist's-eye views of stratigraphic successions on Mars (e.g. Christensen et al, 2004;Squyres et al, 2004Squyres et al, , 2006Squyres et al, , 2009Grotzinger et al, 2005;Haskin et al, 2005). Building on this success, the extraordinary instrument package and anticipated roving capability of the Mars Science Laboratory (MSL) position us to use new rover observations to test hypotheses generated on the basis of highresolution orbital data.…”
Section: Introductionmentioning
confidence: 99%
“…Roush et al (1989) and Pollack et al (1991) reported the detection of sulfate features in the 8-10 μm-region, which is consistent with the presence of 10 to 15 wt% of sulfates in the airborne dust. Christensen et al (2004), using the Miniature Thermal Emission Spectrometer (Mini-TES) aboard the Opportunity rover, detected magnesium and calcium sulfates in outcrops at Meridiani Planum. Finally, using the OMEGA infrared imaging spectrometer aboard the Mars Express orbiter, Bibring et al (2005) identified sulfates in many places on the Martian surface.…”
Section: Introductionmentioning
confidence: 99%